The star cluster system of the luminous elliptical galaxy NGC 1600 - Santiago, Basilio Xavier (2008)
Context. Luminous elliptical galaxies generally display a rich star cluster system, whose properties provide strong constraints on the physics of galaxy formation and evolution. Star cluster system studies, however, concentrate on galaxies located in nearby or rich galaxy clusters. Aims. We acquired deep B and I images of NGC 1600, a luminous elliptical in a galaxy group to study its star cluster system. The images were obtained with the Optical Imager at the Southern Telescope for Astrophysical Research for an exposure time of 1.66 h in each filter. Methods. The sample selection incompleteness was assessed as a function of magnitude and image background level. Source counts were measured for different elliptical annuli from the centre of NGC 1600, background subtracted, and fitted with a Gaussian function. Colour distributions were derived as a function of galactocentric distance for sources measured successfully in both filters. Typical ages and metallicities were estimated based on single stellar population models. Results. A clear excess of point sources around NGC 1600 was found in relation to the nearby field. The source counts were consistent with a Gaussian distribution typical of other luminous ellipticals. The luminosity function fits provided an estimate of the density of clusters at the different annuli that could be integrated in solid angle, resulting in an estimated total population of NGC -~ 2850 star clusters. This yielded a specific frequency of SN -~ 1.6. The colour distributions show a hint of bimodality, especially at 20 -~ kpc from the centre. Clusters in this region may be associated with a ring or shell perturbation. Finally, the star cluster candidates were crosscorrelated to discrete X-ray sources and a coincidence rate of -~ 40% was found. These are likely to be globular clusters harboring low-mass X-ray binaries. Conclusions.